THE ECONOMIC HISTORY OF TURKESTAN IN PETER HOPKIRK'S WORK “THE BIG GAME” (Scientific journal of the Fergana State University, 2024)
This research aims to highlight the socio-economic state of Turkestan as part of the Russian Empire in the second half of the 19th – early 20th centuries based on the work “The Great Game: On Secret Service in High Asia” by British journalist, historian and writer Peter Hopkirk, which was published twice, in 1990 and 2006.The Russian and British empires, as the largest world powers throughout the 19th and early 20th centuries waged a military-political and economic confrontation in most of the East and, in particular, in Central Asia. In historiography, this rivalry is better known as the “Great Game”. As is known, the result of this geopolitical confrontation was the conquest by the Russian Empire of the southern and central parts of Central Asia - three Uzbek khanates - with the establishment of the Turkestan Governor-General in the newly conquered territories in 1867. In subsequent decades, these khanates completely lost their statehood, for example, the Kokand Khanate was annexed in 1876 by the troops of the Turkestan General-Governorship or turned into semi-independent protectorates of the Russian Empire as a result of a military invasion of the territories of these states - the Bukhara Emirate lost its independence in 1868, and the Khiva Khanate in 1873. Thus, Central Asia or the so-called “no man's land” - a hypothetical buffer between the geopolitical interests of the Russian and British empires - was drawn into the orbit of Russian political and economic interests.